Conocemos los animales domésticos y salvajes - Pérez Vásquez, Susana Lizeth (2019)
The present activity “how animals are born” for boys and girls of 03 years of the Initial Education Level has as its learning purpose the development of the competition “Investigate through scientific methods to build their knowledge”_x000D_ Considering the performance “he asks questions that express his curiosity about the objects, living beings, facts or phenomena that occur in his environment; and when he responds, he reveals what he knows about them”_x000D_ This learning session is referred to the needs of children in the area of science and technology, also in socio-constructive theories in the framework of the competency curriculum, considering the pedagogical processes, didactic processes of the area of science and technology and with emphasis the formative evaluation.